1994
DOI: 10.2527/1994.724911x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal nutrition on muscle fiber number development in the porcine fetus and on subsequent postnatal growth1

Abstract: In the pig, undernutrition in utero causes low birth weight, a decrease in muscle fiber number, and a reduction in postnatal growth rate. The effect on fiber number is mediated via a reduced secondary fiber population. Within a litter of pigs, lighter-weight pigs have probably suffered some deficit in muscle fiber number. In an attempt to improve the number of fibers in the lighter-weight pig fetuses, four maternal feeding regimens were used, one serving as the control. Maternal feed intake was doubled for one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
154
2
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 0 publications
17
154
2
3
Order By: Relevance
“…The current results regarding kid growth emphasised the importance of additional feeding before mating and during lactation in extensive goat farming (Martin et al 2004;Scaramuzzi et al 2006;Sultana et al 2012). It has been reported that the nutritional level in maternal feeding during pregnancy affected the number of secondary muscle fibres in striated muscle tissue in foetus which had an effect on birth weight (Dwyer et al 1994;Tygesen & Harrison 2005;Tygesen et al 2007). Also, as given in Table 6, weaning kids from treatment goats were heavier than those of control goats (p<0.05).…”
Section: Resultsmentioning
confidence: 73%
“…The current results regarding kid growth emphasised the importance of additional feeding before mating and during lactation in extensive goat farming (Martin et al 2004;Scaramuzzi et al 2006;Sultana et al 2012). It has been reported that the nutritional level in maternal feeding during pregnancy affected the number of secondary muscle fibres in striated muscle tissue in foetus which had an effect on birth weight (Dwyer et al 1994;Tygesen & Harrison 2005;Tygesen et al 2007). Also, as given in Table 6, weaning kids from treatment goats were heavier than those of control goats (p<0.05).…”
Section: Resultsmentioning
confidence: 73%
“…However, in the context of foetal fibre number, the precise role of maternal nutrition is not entirely clear. Earlier work suggests that doubling food intake during early sow pregnancy increases the number of secondary fibres in the newborn, which would confer greater potential for post-natal growth (Dwyer et al, 1994). More recent work, however, could not reproduce this finding (Nissen et al, 2003).…”
Section: Fibre Number: Mediators Of Muscle Hyperplasiamentioning
confidence: 94%
“…Age and weight prior to slaughter, growth rates between birth and slaughter and eye muscle depth at the P2 position were similar, irrespective of maternal diet. These results are unsurprising, since body weight was the criterion on which pigs were selected for slaughter, the growth rates of pigs were similar throughout the neonatal period, and the programming of lean growth potential is thought to occur during early-mid gestation (Dwyer et al, 1993 and1994). The offspring of C and S sows possessed more fat at the P2 position prior to slaughter; this was surprising because the S group exhibited the slowest rate of fat accretion during the pre-weaning period.…”
Section: --mentioning
confidence: 99%